Abrasion-resistant CMAS glass-ceramic coatings incorporated with B4C particles - Copoglu, Nurullah; Karaahmet, Oguz; Cicek, Bugra (SAGE PUBLICATIONS INC, 2022)
One of the most significant mechanical characteristics of glass-ceramic coatings (GCCS) is abrasion resistance, which is particularly pertinent when contamination from the coated metallic surface is not desired. The influence of incorporating boron carbide (B4C) as a hard particle into the CaO-MgO-Al2O3-SiO2 GCC on the abrasion resistance was examined in this study. A PEI Abraser was used to evaluate the abrasion resistance over 5000 cycles, with mass loss recorded every 1000 cycles. Mass loss following the abrasion test was observed to decrease when the amount of added B4C was increased, indicating that the abrasion resistance was enhanced by B4C addition. The addition of 16 wt-% B4C has had the strongest interface among the matrix/B4C particles, resulting in higher abrasion resistance due to reduced crack formation and porosity, and yielded a decrease in mass loss of about 54%, colour change of <2 in terms of Delta E and gloss change about 40%.
Keywords: CMAS; diopside; glassceramic; coating; abrasion resistance; boron carbide; BORON-CARBIDE; ENAMEL; CRYSTALLIZATION; MICROSTRUCTURE; OXIDATION; BEHAVIOR; PHASE; B2O3; Materials Science